2000
DOI: 10.1007/s12144-000-1003-y
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation among adolescents in relation to recalled exposure to violence

Abstract: The relationship between exposure to violence and vulnerability to suicide among adolescents was examined. The topic was initiated by the rapid increase in adolescent's exposure to violence and the sparse systematic research available on its relationship to attitudes about life and death. The study's main hypothesis is that high levels of exposure to violence are associated with high suicide risk according to two conceptual paradigms--Fear of Death and Attraction and Repulsion to Life. Eighty-five adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…SI is one of many adverse outcomes consistently linked to victimization in the empirical literature (Bernegger et al, 2015; Cohen, 2000; Pastore, Fisher, & Friedman, 1996). Previous findings indicate that childhood victimization (Thompson, Litrownik, et al, 2012) and physical and psychological abuse (Thompson, Proctor, et al, 2012) significantly predict SI during adolescence.…”
Section: Psychological Distress As a Pathway To Si Among Victimized Y...mentioning
confidence: 99%
“…SI is one of many adverse outcomes consistently linked to victimization in the empirical literature (Bernegger et al, 2015; Cohen, 2000; Pastore, Fisher, & Friedman, 1996). Previous findings indicate that childhood victimization (Thompson, Litrownik, et al, 2012) and physical and psychological abuse (Thompson, Proctor, et al, 2012) significantly predict SI during adolescence.…”
Section: Psychological Distress As a Pathway To Si Among Victimized Y...mentioning
confidence: 99%
“…Likgiltighet inför döden har uppmärksammats bland heroinanvändare i tidigare studier Plumridge & Chetwynd 1999;. Likgiltighet har visat sig ha en stor betydelse för suicidrelaterat beteende (Cohen 2000).…”
Section: Psykisk Ohälsa Självmedicinering Och Likgiltighet Inför Dödenunclassified
“…Indifference Another complex phenomenon surrounding SRB in heroin users is the influence of indifference, or fatalism (whereby an individual engages in activities which are harmful to themselves over a long period but do not fit within the acute model commonly constructed as "suicide") and where this fits within models of SRB. From Durkheim's original research into suicide (1952/1897), indifference and attitudes towards life and death, have been found to play an important role in suicidal behavior (Cohen, 2000). It has been demonstrated that suicidal adolescents fear death to a lesser degree than nonsuicidal people (Orbach, 1988).…”
Section: Figurementioning
confidence: 99%